Social marketing strategies and their contribution to customer loyalty of the agencies of the NGO Pro Mujer in the Arequipa area, 2014 - Gutiérrez Gómez, Alcides (2016)
Objective: This study aimed to determine whether social marketing strategies have contributed to the loyalty of the NGO agencies pro fencing woman Arequipa, 2014. Method: The research is applied. It is descriptive in nature, so that customer perceptions of the NGO Pro Mujer fencing of Arequipa, on strategies of social marketing used in 2014. It is also correlational, was measured so that the relationship between analyzed social marketing strategies and customer loyalty NGO Pro Mujer fencing of Arequipa in 2014. for this, customers surveyed 140 agencies NGO Pro Mujer fencing of Arequipa, 2014, using a questionnaire of 22 dichotomous questions (social marketing strategy) and 22 Likert scale (customer loyalty), evaluating each block of the indicators raised questions in the investigation. Results: To test the contribution of each strategy, proceeded to perform the nonparametric statistical test of chi square, which determined that the strategy "product" if it contributes to customer loyalty, to obtain a value-P 0.0498 ; and 56 strategies "price", "promotion" and "distribution" does not contribute to customer loyalty to obtain the p-value of 0.2660, 0.7942 and 0.7286 respectively. Conclusion: Strategies social marketing agencies NGO Pro Mujer fencing of Arequipa, in 2014, have not contributed to the loyalty of its customers